الحاد و لادینیت اور اسلامی علم الکلام :عبد العزیز پرہاروی کا اختصاصی مطالعہ - Hafiz Muhammad Hassan Mahmood; Ijaz Ali Khoso (Pakistan Journal of Islamic Research)
A firm theological foundation is needed to overcome the challenges of secularism and modernity in contemporary age. It is important to provide logical arguments for religious concepts to prevent atheism. It is evident in history of Islam that all the efforts made by the groups like Motezilla, Kirāmia and Lā-adria etc for dismantling Islamic thoughts were wisely encountered eminent Scholars of Islamic world. They spread the true beliefs and teachings of Islam. The writings of scholars from subcontinent also played an important role in this regard and one of them Allama Abdul Aziz Parhārvī. This article primarily discusses the meaning and significance of Atheism. Moreover, the concept of Atheism is mainly explained with its root causes and effects. Teaching of Allama Parhārvī are Analyzed for the solution to the challenges of Atheism. This study also explains the effectiveness of Parhārvī’s writings to eradicate the implication of secular and atheist thoughts. Parhārvī was a great scholar of Islamic theology in our region. He wrote an explanatory book named “Al-nibrās” of “Sharah aqāid-e-nasfia” i.e an important book of theology thought in the religious institutions (Madāris). “Al-nabrās” is an important book which gives a clear insight and logical explanation of Islamic beliefs and proves that they are the need of human nature and phycology.